PERAN GURU IPS DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK (Study Multi Situs Di MTsN Tulungagung Dan MTsN Karangrejo) - agus suhartono (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2018)
This study aimed to describe the role of teachers IPS in create the character of students as educator,motivator, fasilitator, informator, konselor and evaluator.  method used was qualitative research based on discussion, it included as descriptive research using multi sites study.  The data collection techniques are participant observation, in-depth interviews, and documentation. Data analysis was done starting from the reduction  , the presentation  , and conclusions. To test the validity carried out triangulation. The create character religius, honest,  discipline, demokratic, holy land love, pay attention and responsible of students in MTsN Tulungagung and MTsN Karangrejo apply  theory interaksionalisme simbolic by coley, blumer, Blumstein, George Herbert Mead   dan Manfred Kuhn.